Radiation Safety For Operating Room Technicians - SOYAL, Halil; ORTABAĞ, Tülay (International Journal of Computational and Experimental Science and Engineering, 2023)
Abstract Radiation safety is an important consideration for operating room technicians, in procedures that involve the use of fluoroscopy or other imaging technologies that emit ionizing radiation. Radiation safety is essential to safeguard human health, minimize radiation exposure, optimize medical radiation use, protect the environment, and comply with regulatory standards. By implementing appropriate safety measures, radiation can be used safely and responsibly in various fields, balancing the benefits of radiation applications with the need for protection against potential harm. It is important for operating room technicians to adhere to radiation safety guidelines and best practices to protect themselves, their colleagues, and patients from unnecessary radiation exposure. Collaboration with radiation safety officers, radiation safety committees, and other relevant experts can help ensure a culture of safety and ongoing improvement in radiation safety practices. The aim of this article is to inform the operating room technicians about radiation, to keep their occupational exposure to a minimum is to help.